Motor neuron disease - Talbot, Kevin (Facts (Oxford, England), 2008)
Motor neuron disease (MND) is a common but devastating disability that has a profound impact on people's lives. This book provides an easily-accessible guide to the disease for patients with motor neuron disease and their carers. The authors have organised it around a series of the commonest questions asked in their clinic, emphasising the variation in the course of MND and the individual nature of the patient journey through the disease. After an initial description of thesymptoms for MND and how neurologists make the diagnosis the authors describe what is known about the causes and how scientists are trying to understand the disease. The book also looks at how a team of specialists can provide support and symptom control for the patient.